Meizhou Dongpo Restaurant Group - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
At the end of 2013, leaving the opening festivities for the 93rd Meizhou Dongpo branch restaurant in Shunyi, Beijing, Wang Gang was in a good mood. He felt a bit weary as he was driven back home, gazing at the night out of the car window. Looking back at Meizhou Dongpo's development over the past seventeen years, Wang Gang reflected on various aspects of his life.